PENGEMBANGAN LEMBAR KERJA MAHASISWA (LKM) BERBASIS KONTEKSTUAL PADA MATA KULIAH KIMIA ANORGANIK - Erviyenni '; Elva Yasmi (Jurnal Pendidikan Kimia Universitas Riau, 2016)
The development of research aimed at developing Contextual-based Student Worksheet valid, practical, and effective for learning chemistry inorganic. The method used is development research (development research). The research was conducted in six months and consists of four stages, namely the definition phase (define), the design (design), development (develop), pendesiminasian (desseminate). New research to the development stage. The research data were collected through evaluation sheets filled in by the validator. The results showed that the Student Worksheet based Contextual of learning material developed for the reduction of oxidation, elements and complex compounds have valid criteria in terms of format, technical and content.Keywords: Development, student Worksheet, contextual, Inorganic chemistry